Pharmacoenhancement of low crizotinib plasma concentrations in patients with anaplastic lymphoma kinase-positive non-small cell lung cancer using the CYP3A inhibitor cobicistat - Hohmann, Nicolas; Bozorgmehr, Farastuk; Christopoulos, Petros; Mikus, Gerd; Blank, Antje; Burhenne, Jürgen; Thomas, Michael; Haefeli, Walter E. (Clinical and translational science, 2021)
The inhibitor of anaplastic lymphoma kinase (ALK) crizotinib significantly increases survival in patients with ALK-positive non-small cell lung cancer (NSCLC). When evaluating crizotinib pharmacokinetics (PKs) in patients taking the standard flat oral dose of 250 mg b.i.d., interindividual PK variability is substantial and patient survival is lower in the quartile with the lowest steady-state trough plasma concentrations (Cmin,ss), suggesting that concentrations should be monitored and doses individualized. We investigated whether the CYP3A inhibitor cobicistat increases Cmin,ss of the CYP3A substrate crizotinib in patients with low exposure. Patients with ALK-positive NSCLC of our outpatient clinic treated with crizotinib were enrolled in a phase I trial (EudraCT 2016-002187-14, DRKS00012360) if crizotinib Cmin,ss was below 310 ng/mL and treated with cobicistat for 14 days. Crizotinib plasma concentration profiles were established before and after a 14-day co-administration of cobicistat to construct the area under the plasma concentration-time curve in the dosing interval from zero to 12 hours (AUC0-12). Patients were also monitored for adverse events by physical examination, laboratory tests, and 12-lead echocardiogram. Enrolment was prematurely stopped because of the approval of alectinib, a next-generation ALK-inhibitor with superior efficacy. In the only patient enrolled, cobicistat increased Cmin,ss from 158 ng/mL (before cobicistat) to 308 ng/mL (day 8) and 417 ng/mL (day 14 on cobicistat), concurrently the AUC0-12 increased by 78% from 2,210 ng/mL*h to 3,925 ng/mL*h. Neither safety signals nor serious adverse events occurred. Pharmacoenhancement with cobicistat as an alternative for dose individualisation for patients with NSCLC with low crizotinib exposure appears to be safe and is cost-effective and feasible.
First published: 22 November 2020
Gesehen am 19.08.2021